Understanding the interplay between stress, anxiety, and depression and their impact on health in traffic police officers - Ramos-Galarza, Carlos; Flores, Fiamma; Argoti, Taysha; Díaz-Guerra, Diego D.; Hernández-Lugo, Marena de la C.; Broche-Pérez, Yunier (Frontiers in Psychiatry, 2025)
BackgroundTraffic police officers are frequently exposed to stress, anxiety, and depression, which adversely impact their health. This study hypothesized that these factors influence the hormonal, muscular, digestive, and cognitive systems of traffic police officers.MethodsThe sample comprised 146 traffic police officers (42 women and 104 men) aged 30 to 38. Gender differences in symptoms were examined, and model fit was assessed using indicators such as chi-square, comparative fit index, root mean square error of approximation (RMSEA), and standardized root means residual (SRMR).ResultsGender differences were observed, with women reporting more significant issues related to muscular (t = 2.77, p = .003), hormonal (t = 2.29, p = .001), and cognitive symptoms (t = 1.37, p = .08). The models demonstrated a good fit, particularly in the model examining digestive symptoms (CFI.95, RMSEA.06 (.05 -.08), SRMR.04).ConclusionsThe findings indicate a substantial impact of stress, anxiety, and depression on traffic police officers’ health. Psychological support and monitoring are recommended at traffic police stations.Practical and academic contributionThis research offers essential academic contributions by advancing understanding of the psychophysiological effects of stress, anxiety, and depression in high-stress occupations, using predictive modeling. Practically, the findings support the development of targeted mental health interventions and preventive strategies tailored to traffic police officers, contributing to improved occupational health and job performance.